Anorectal manometry profile among elderly patients with chronic constipation in a tertiary health center - Kulkarni, Harish Srikanth; Singh, Prafulla Kumar; Katepally, Saikrishna; Kumar, P. Shravan (International Journal of Research in Medical Sciences, 2023)
Background: Constipation is a common condition in elderly in India. High resolution anorectal manometry (HRAM) is an essential tool in the evaluation. In this context, studies from south India are sparse regarding the motility data of elderly patients with functional constipation. We aimed at studying anorectal pressure patterns in this population of this part of the country. Methods: Manometric data of 50 elderly patients (≥60 year), who underwent the procedure for chronic constipation (Rome IV), was retrospectively collected. Manometric parameters were compiled and observations tabulated. Results: Among 50 patients, 35 were (70%) males and 15 (30%) females with mean age of 66.5±3.2 years. In HRAM study, the mean resting pressure was 90.2±27.5 mmHg (range 43-153 mmHg) and mean squeeze pressure was 136.9±39.76 mmHg (range 88-223 mmHg). In present study 23 patients had abnormal HRAM suggestive of dyssynergic defecation (46%). Conclusions: The present study showed that 46% of the elderly constipation patients had defecation disorder. Defecation disorders are common in our population and there is a need to diagnose it as treatment perspectives differ from other causes of constipation.